1994
DOI: 10.1111/j.1744-6570.1994.tb01573.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF APPLICANTs' REACTIONS TO COGNITIVE ABILITY TESTS AND AN ASSESSMENT CENTER

Abstract: Manufacturing applicants' perceptions of two selection devices were examined. In Study 1, applicants (n= 3,984) completed cognitive ability tests and a survey of reactions. In Study 2, a subset of applicants from Study 1 (n= 194) participated in an assessment center and completed the survey. Applicants reacted favorably to the procedures but viewed the assessment center as more face valid than the cognitive tests. Applicants who perceived the selection techniques more favorably were also more satisfied with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
261
2
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(271 citation statements)
references
References 29 publications
6
261
2
2
Order By: Relevance
“…Demographic variables collected included age, gender, ethnicity, employment status, education, and whether the applicant had taken a test for this jurisdiction before. Overall selection system process fairness (␣ ϭ .91) was measured by 3 items based on Smither et al (1993) and Macan et al (1994;e.g., "I think that the Civil Service hiring process is a fair way to select people for the job of police recruit"). Organizational attractiveness (␣ ϭ .88) was measured by 5 items adapted from Smither et al (1993;e.g., "The police department is a good place to work").…”
Section: Methodsmentioning
confidence: 99%
“…Demographic variables collected included age, gender, ethnicity, employment status, education, and whether the applicant had taken a test for this jurisdiction before. Overall selection system process fairness (␣ ϭ .91) was measured by 3 items based on Smither et al (1993) and Macan et al (1994;e.g., "I think that the Civil Service hiring process is a fair way to select people for the job of police recruit"). Organizational attractiveness (␣ ϭ .88) was measured by 5 items adapted from Smither et al (1993;e.g., "The police department is a good place to work").…”
Section: Methodsmentioning
confidence: 99%
“…Seitens der Arbeitgeber besteht Unsicherheit über die wirkliche Produktivität des Arbeitnehmers, Arbeitnehmer hingegen haben kein genaues Wissen über das Arbeits-und Aufgabenumfeld (Spence, 1973). Somit sind die innerhalb von Rekrutierungsmethoden gesendeten Informationen eine kritische Ressource, wenn der Bewerber sich ein Bild über die Arbeitgeberattraktivität eines Unternehmens bildet (Mecan, Avedon, Paese, & Smith, 1994;Richman-Hirsch, Olson-Buchanan, & Drasgow, 2000;Smither, Reilly, Millsap, Pearlman, & Stoffey, 1993). Dahingehend werden sämtliche Signale in die Informationsverarbeitung und somit in die Entscheidungsfindung mit einbezogen, um Informationsasymmetrien auszugleichen (Turban & Greening, 1996) und Unsicherheiten zu reduzieren (Daft & Lengel, 1986).…”
Section: Theoretischer Bezugsrahmen 31 Signalingunclassified
“…Auf Basis der vom Rekrutierer gesendeten Signale entwickelt der Bewerber ein genaueres Bild über das Unternehmen (Rynes et al, 1980;Turban & Dougherty, 1992). Die vom Bewerber gewonnenen Eindrücke bezüglich des Rekrutierers wirken auf die wahrgenommene Arbeitgeberattraktivität und die subjektive Norm und infolgedessen auf die Absicht, den Bewerbungsprozess weiter zu verfolgen (Mecan et al, 1994;Richman-Hirsch et al, 2000;Smither et al, 1993).…”
Section: Implikationen 71 Implikationen Für Die Forschungunclassified
“…Meta-analytic reviews have indicated that work samples have high criterion-related validity for predicting job performance (Roth, Bobko, & McFarland, 2005;Schmidt & Hunter, 1998). Furthermore, as work samples have a higher degree of fidelity to tasks performed on the job than traditional individual differences predictors (Asher & Sciarrino, 1974), they are generally associated with more favorable applicant reactions (e.g., Hausknecht, Day, & Thomas, 2004;Macan, Avedon, Paese, & Smith, 1994).…”
mentioning
confidence: 99%